Kontribusi kepercayaan diri siswa terhadap kematangan emosional siswa - Azizah, Siti Nur; Putri, Yoan Dini; Arifin, Jaenal; Marisa, Cindy (Orien: Cakrawala Ilmiah Mahasiswa, 2024)
the purpose of this research is to determine the description of students' self-confidence at SMP Perjuangan Informatika Terpadu Depok City, to determine the influence of self-confidence on the emotional maturity of students at SMP SMP Perjuangan Informatika Terpadu Depok City. This research uses quantitative methods with a correlational approach. In this research, the total sample of 30 students was taken using random sampling technique. Data collection was carried out using questionnaire distribution techniques, data analysis using descriptive statistical methods, Pearson's multiple correlation coefficient, coefficient of determination and regression analysis. Testing was carried out using t and f tests as well as SPSS results. Based on data analysis, it can be concluded that there is a significant influence between student self-confidence and emotional intelligence at SMP Perjuangan Informatika Terpadu.